MSMEs Towards Halal Certification for Pokdarwis Agrotourism Village - Isnurhadi; Mohamad Adam; Marlina Widiyanti; Iisnawati iisnawati (Universitas Serang Raya, 2026)
MSMEs in Agrotourism Village, Sungai Jawi Kalidoni, Palembang face challenges in improving product quality, especially in halal certification requirements. One of the main obstacles faced is their lack of understanding and knowledge about the certification process. The purpose of this training is to provide technical guidance for business actors, members of the Pokdarwis Sungai Jawi to understand the certification process and prepare for the HALAL certification. The certification could increase consumer confidence and expand the knowledge market of business actors. The training delivered in two stages, start from management assistance such as explanations about halal and the process of applying for halal certification. The next stage is technical assistance where participants try the SIHALAL application for Halal certification applications. After the training, MSMEs member of Pokdarwis Sungai Jawi could prepare their documents and start applying for HALAL certification.